2012
DOI: 10.1038/srep00954
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 isoforms in whole blood as potential biomarkers of Parkinson disease

Abstract: DJ-1 is a multifunctional protein that plays an important role in oxidative stress, cell death, and synucleinopathies, including Parkinson disease. Previous studies have demonstrated that total DJ-1 levels decrease in the cerebrospinal fluid, but do not change significantly in human plasma from patients with Parkinson disease when compared with controls. In this study, we measured total DJ-1 and its isoforms in whole blood of patients with Parkinson disease at various stages, Alzheimer disease, and healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 42 publications
0
61
0
2
Order By: Relevance
“…The protein concentration of individual samples was determined using the Pierce bicinchoninic acid (BCA) Protein Assay Kit (Thermo Scientific, Rockford, IL). The proteins were then reduced and alkylated using dithiothreitol and iodoacetamide, respectively, followed by trypsin digestion as described previously (24,27).…”
Section: Methodsmentioning
confidence: 99%
“…The protein concentration of individual samples was determined using the Pierce bicinchoninic acid (BCA) Protein Assay Kit (Thermo Scientific, Rockford, IL). The proteins were then reduced and alkylated using dithiothreitol and iodoacetamide, respectively, followed by trypsin digestion as described previously (24,27).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of seven DJ-1 isoforms detected in blood, those with post-translational 4-hydroxy-2-nonenal modifications were altered in late PD. 61 In an independent study, DJ-1 oxidized on cysteine-106 specifically was found to be elevated in red blood cells in PD. 62 Initial results are therefore somewhat encouraging, with the caveat that careful consideration of …”
Section: Pd Genetics and Biomarker Developmentmentioning
confidence: 99%
“…Park7 expression is reduced in pancreatic islets of type 2 diabetic patients, where it may be required for mitochondrial function and glucosestimulated insulin secretion (42). Cerebrospinal, but not plasma, Park7 levels have been proposed as a biomarker of Parkinson disease (43,44), whereas 4-hydroxy-2-nonenal-modified Park7 could be a plasma biomarker of late-stage Parkinson (45).…”
Section: Discussionmentioning
confidence: 99%